Woman social representations in Genova and Calarcá, Quindío, from occupational roles played in agricultural labors and cultural activities related to coffee (Revista de Investigaciones Universidad del Quindío, 2011)
This paper deals with an analysis of woman social representation in the towns of Genova and Calarcá in the department of Quindío on occupational roles women play in agricultural and cultural activities related to coffee. This topic is considered an element that has centralized the culture of the department of Quindío, and it has shaped its economic performance suggesting modes of action according to gender, but these modes have changed due to perception people have about women in the XXI century. To achieve this objective, the analysis formats proposed by Tania Rodríguez are appealed. These formats are based on core theory of Jean Abric (2001). In the same way, the notion of gender is related to a conceptual base viewed from the common culture to build social representations.
Keywords: social representations; woman; Quindío; coffee culture; farming; coffee; tourism